2019
DOI: 10.1016/j.celrep.2019.06.088
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome-wide Landscape and Modalities of EJC Binding in Adult Drosophila

Abstract: Highlights d ipaRt: a method for protein-RNA-binding landscape definition in cells and organisms d Drosophila EJC-bound mRNAs are biased toward differentiation and development d Drosophila EJC assembly on mRNAs favors genes with complex gene architecture d Splice site strength, RNA structure, and CG-rich hexamers enhance EJC binding in flies

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 98 publications
0
26
0
Order By: Relevance
“…EJCs bind to mRNAs at specific sites approximately 20–24 nts upstream of the spliced exon-exon junction [ 4 , 5 ]. The observation that this binding is independent of the sequence context and occurs at a specific position relative to the spliced-out intron has puzzled researchers for many years.…”
Section: Spliceosomal Ejc Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…EJCs bind to mRNAs at specific sites approximately 20–24 nts upstream of the spliced exon-exon junction [ 4 , 5 ]. The observation that this binding is independent of the sequence context and occurs at a specific position relative to the spliced-out intron has puzzled researchers for many years.…”
Section: Spliceosomal Ejc Assemblymentioning
confidence: 99%
“…These revealed that the EJC does not only bind to the canonical deposition site, 20–24 nts upstream of an exon-exon junction, but also at other positions in exons [ 5 , 19 ]. In mammals, these non-canonical binding sites are quite frequent, ranging up to 50% [ 5 ], while in Drosophila nearly all EJCs seem to be deposited at canonical binding sites [ 4 ]. Interestingly, CASC3 containing EJCs also show a strong bias towards canonical deposition, further supporting the assumption that it is not present in all EJC cores [ 44 ].…”
Section: Spliceosomal Ejc Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…We find that both Eif4a3 and Magoh, but not a negative control RNA-binding protein HuC, specifically co-immunopreciptate with Rbm8a ( Fig 1A). We and others have previously shown that the EJC primarily binds 24 nts upstream of exon-exon junctions in cultured human cells and adult Drosophila [42][43][44][45][46]. To test if the EJC binds at a similar position on zebrafish spliced RNAs, we first optimized RNA-immunoprecipitation (RIP) from RNase-treated zebrafish embryo lysates using an Rbm8a antibody (S1B and S1C Fig).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown in human cells that this protein UV-crosslinks to RNA very inefficiently as compared to a sequence-specific RBP HNRNPA1 (Singh et al 2014). Recently, this poor in vivo UV crosslinking ability of EIF4A3 was also reported in Drosophila adult animals (Obrdlik et al 2019). Instead, chemical crosslinking using dithio(bis-) succinimidyl propionate was found to stabilize EIF4A3 within EJCs for identification of Drosophila EJC binding sites.…”
Section: Factors That Impact Uv Crosslinking Ability Of Rna-associatementioning
confidence: 99%